Kemanusiaan Generasi Z yang Terdistraksi oleh Artificial Intelligence - Febri Ompu Sunggu (Retorik: Jurnal Ilmu Humaniora, 2022)
Generation Z is faced with challenging times and technological advancements that lead them to be individualistic and indifferent to their surroundings. Technology distracts Generation Z's humanity and leads them to a disposition of no longer being fully human. Not only that, Generation Z also often experiences a loss of orientation in their daily lives. The question is why Generation Z is losing their humanity, how artificial intelligence is affecting them, and to what extent artificial intelligence is impacting the lives of Generation Z today. The research methodology used by the author is the literature study method. The purpose of this research is to find out how far the influence of artificial intelligence is in the lives of Generation Z, what aspects of life are affected by advances in technology, as well as possible solutions to the challenges confronted by Generation Z. The contribution of this research is aimed primarily at Generation Z who are familiar with various technological advances but feel confused about their real manifestation as human beings, with their nature as human beings and obligations for which they are accountable. The researcher suggests that the various conveniences created and offered by artificial intelligence can lead Generation Z to become complete and comprehensive human beings capable of taking responsibility for their humanity.